Coordenadas geográficas de Turnera sidoides subsp. carnea - Via Do Pico, Gisela Mariel (2022)
The lowlands of mid-latitude South America comprise complex temperate ecoregions characterized by a unique biodiversity. However, the processes responsible for shaping its species diversity are still largely unknown. Turnera sidoides subsp. carnea is a variable subspecies occurring in the lowlands of northeastern Argentina and Uruguay, extending to southern Paraguay and Brazil. It constitutes a good model to perform evolutionary studies. Here we used an integrative approach to understand the process of diversifi cation within this subspecies and to increase the knowledge concerning patterns and processes responsible for shaping the species diversity in the temperate lowlands of South America. The results provided strong evidences that this subspecies is an autopolyploid complex per se, being in an active process of intrasubspecifi c diversifi cation. Morphological and genetic data show that the diversity of T. sidoides subsp. carnea is in congruence with the great past and present abiotic and biotic variability of the mid-latitude South American lowlands. The evolutionary history of this subspecies is consistent with past fragmentation and allopatric differentiation at diploid level. Geographic isolation and local adaptation would have promoted strong morphological, ecological, and genetic differentiation, resulting in two morphotypes and different genetic groups indicative of incipient speciation.